Vocal rhythms in nesting Lusitanian toadfish, Halobatrachus didactylus - Vieira, Manuel (2021)
Males of several fish species aggregate and vocalize together, increasing the detection range of the sounds and their chances of mating. In the Lusitanian toadfish (Halobatrachus didactylus), breeding males build nests under rocks in close proximity and produce hundreds of boatwhistles (BW) an hour to attract females to lay their demersal eggs on their nests. Chorusing behaviour includes fine-scale interactions between individuals, a behavioural dynamic worth investigating in this highly vocal fish. Here we present a study to further investigate this species' vocal temporal patterns on a fine (individual rhythms and male-male interactions) and large (chorus daily patterns) scales. Several datasets recorded in the Tagus estuary were labelled with the support of an automatic recognition system based on hidden Markov models. Fine-scale vocal temporal patterns exhibit high variability between and within individuals, varying from an almost isochronous to an apparent aperiodic pattern. When in a chorus, males exhibited alternation or synchrony calling patterns, possibly depending on motivation and social context (mating or male-male competition). When engaged in sustained calling, males usually alternated vocalizations with their close neighbours thus avoiding superposition of calls. Synchrony was observed mostly in fish with lower mean calling rate. Interaction patterns were less obvious in more distanced males. Daily choruses showed periods with several active calling males and periods of low activity with no significant diel patterns in shallower intertidal waters. Here, chorusing activity was mainly affected by tide level. In contrast, at a deeper location, although tidal currents causes a decrease in calling rate, tide level did not significantly influence calling, and there was a higher calling rate at night. These data show that photoperiod and tide levels can influence broad patterns of Lusitanian toadfish calling activity as in other shallow-water fishes, but fine temporal patterns in acoustic interactions among nesting males is more complex than previously known for fishes.